Flow-driven right-to-left cardiac shunting in a patient with carcinoid heart disease and patent foramen ovale without elevated right atrial pressure: a case report and literature review. Issue 6 (22nd November 2020) - Dherange, Parinita; Telles, Nelson; Modi, Kalgi
Abstract: Background: Carcinoid heart disease is present in approximately 20% of the patients with carcinoid syndrome and is associated with poor prognosis. It usually manifests with right-sided valvular involvement including tricuspid insufficiency and pulmonary stenosis. Patent foramen ovale (PFO) is present in approximately 50% of the patients with carcinoid heart disease which is twice higher than the general population. Right-to-left shunting through a PFO can occur either due to higher right atrial pressure than left (pressure-driven) or when the venous flow is directed towards the PFO (flow-driven) in the setting of normal intracardiac pressures. We report a rare case of flow-driven right-to-left atrial shunting via PFO in a patient with carcinoid heart disease. Case summary: A 54-year-old male with a metastatic neuroendocrine tumour to liver presented with progressive shortness of breath for 5 months. Patient was found to be hypoxic with oxygen saturation of 78% and examination revealed a holosystolic murmur. Arterial blood gas showed oxygen tension of 43 mmHg. A transthoracic and transoesophageal echocardiogram showed aneurysmal inter-atrial septum with a PFO, severe tricuspid regurgitation directed anteriorly towards the inter-atrial septum leading to a marked right-to-left shunt. Right heart catheterization showed right atrial pressure of 8 mmHg, mean pulmonary artery pressure of 12 mmHg, and normal oxygen saturations in the right atrium, right ventricle, and pulmonary arteries. The patient then underwent closure of the PFO along with tricuspid valve and pulmonary valve replacement at an experienced cardiovascular surgical centre and has been asymptomatic since. Conclusion: Right-to-left shunting through a PFO in patients with normal right atrial pressure can be successfully treated with closure of the PFO. Thus, understanding the mechanism of intracardiac shunts is important to accurately diagnose and treat this rare and fatal condition.